3D-printed radiopaque polymer composites for the in situ monitoring of biodegradable medical implants. (September 2020) - Chang, Chia-Teng; Chen, Hsin-Ting; Girsang, Samuel Pratama; Chen, Yu-Min; Wan, Dehui; Shen, Shu-Huei; Wang, Jane
Highlights: Radiopacifier-embedded PGSA achieve comparable or even higher Hounsfield unit than commercial drainage catheters under compute tomography. Degradation rate of PGSA-BiOCl are faster than PCL-BiOCl. The deviation of predicted mass remains from the experimentally measured mass remains are within 2.2% over four weeks of degradation. PGSA-BiOCl are printed into tubes with high precision through digital light processing system. 3D printed PGSA-BiOCl tubes are more radiopaque than the commercial drainage catheter and can be clearly identified although superimposed with sacral bone. Abstract: The development of biodegradable medical implants that are observable through rapid and non-invasive imaging techniques is crucial toward the treatments of many illnesses. However, the tracking of biodegradable medical devices in post-implantations remains problematic, due to the intrinsic radio-transparency of polymeric device. In this study, we developed a 3D-printable radiopaque polymer with tunable degradation rates and mechanical properties, and can be characterized through X-ray and computed tomography (CT). Three radiopacifiers were introduced to poly(glycerol sebacate) acrylate (PGSA), including barium sulfate, bismuth subcarbonate, bismuth oxychloride, and resulted in radiopacities that are equivalent in intensities to commercial BIOTEQ Ⓡ pigtail drainage catheters. The changes in mechanical properties with varying concentration of radiopacifiers were studied, and bismuth oxychloride embedded PGSA (PGSA-BiOCl) was chosen for in vitro degradation over 30 days. The linear correlation between the mass loss and decrease in radiopacity of PGSA-BiOCl over time indicates the possible application of PGSA-BiOCl toward the monitoring of degrading implants, in contrast with similar PCL products. Through digital light processing additive manufacturing (DLP-AM), PGSA-BiOCl was proven to be 3D-printable and equally visible under radiological imaging when comparing to commercial products. Graphical abstract: Image, graphical abstract